2016
DOI: 10.4067/s0717-95022016000100021
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Vertebral Column and Caudal Skeleton in Prochilodus lineatus Larvae under Laboratory Conditions

Abstract: SUMMARY:For successful fish larviculture thorough studies describing the development of fish in different morphological aspects are required, as they are crucial for larval survival and growth. The present study described in Prochilodus lineatus larvae the osteological development of the vertebral column and caudal skeleton 30 days after hatching (dah). Larvae were obtained by artificial induction of adults. The beginning of formation of the spine occurs between 10 to 12 dah (8.3 mm standard length, SL) simult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…In this study, the red fluorescence emission of the calcium‐binding fluorescent dye Alizarin (1,2‐dihydroxyanthraquinone), when excited with green light, was used in imaging the early and late stages of skeletal ossification in L. calbasu . The skeletal ontology of L. calbasu corroborated with other teleost fishes like Prochilodus lineatus (Hernández et al ., 2016), Sebastes koreanus (Yu & Kim, 2016) and Danio rerio (Bensimon‐Brito et al ., 2016). The ossification of cranial bones and vertebral column started on 2 and 6 dph, respectively, and completed between15 and 20 dph with the complete development of the caudal skeleton.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the red fluorescence emission of the calcium‐binding fluorescent dye Alizarin (1,2‐dihydroxyanthraquinone), when excited with green light, was used in imaging the early and late stages of skeletal ossification in L. calbasu . The skeletal ontology of L. calbasu corroborated with other teleost fishes like Prochilodus lineatus (Hernández et al ., 2016), Sebastes koreanus (Yu & Kim, 2016) and Danio rerio (Bensimon‐Brito et al ., 2016). The ossification of cranial bones and vertebral column started on 2 and 6 dph, respectively, and completed between15 and 20 dph with the complete development of the caudal skeleton.…”
Section: Discussionmentioning
confidence: 99%
“…In some fish, skeletal development starts well before hatching (Postlethwait et al, 2016), whereas there is not one osteological element to exist at hatching in P . stellatus and other fish (Hernández et al, 2016). The previous studies have indicated that there are differences between species in skeletal development.…”
Section: Discussionmentioning
confidence: 99%
“…In this water condition, the complete yolk sac absorption occurs when larva reaches an average standard length (SL) of 5.95 mm (4th DPH), notochord preflexion stage starts around 5.3 mm SL (4th DPH) and flexion occurs with approximately 8.25 mm SL (15th DPH). At the end of the experiment, most of the larvae were in flexion stage; therefore, metamorphosis was not completed (detailed information on larval development of curimba and other closely related Prochilodus genus species can be found in Souza, Melo, Caramaschi, Andrade, & Monteiro, ; Hernández, Olivera, Santinón, Diaz, & Sánchez, and Santos, Sales, Santos, Arantes, & Godinho, ).…”
Section: Methodsmentioning
confidence: 99%
“…At the end of the experiment, most of the larvae were in flexion stage; therefore, metamorphosis was not completed (detailed information on larval development of curimba and other closely related Prochilodus genus species can be found in Souza, Melo, Caramaschi, Andrade, & Monteiro, 2016;Hernández, Olivera, Santinón, Diaz, &Sánchez, 2016 andSantos, Sales, Santos, Arantes, &Godinho, 2016).…”
Section: Experimental Animals and Rearing Conditionsmentioning
confidence: 99%